THE EFFECT OF TASK COMMITMENT ON THE WORK DISCIPLINE OF THE PRINCIPALS OF MADRASAH IBTIDAIYAH IN DELI SERDANG REGENCY INDONESIA - Muhammad Rifai Rifai; Siman Nurhadi Nurhadi; Syafaruddin Syafaruddin Syafaruddin (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to answer the problem of the influence of task commitment on work disciplin to headmaster of Madrasah Ibtidaiyah in Deli Serdang. The population of this research is Islamic Elementary School Principal in Deli Serdang regency as many as 156 people with a total sample of 113 people taken to consult with Krejcle –Morgan Table. The research instrument used was a set of questionnare with Likert scale. The research data were processed and analyzed with path analysis. This Path analysis begins with the test requirements include the analysis of normality test, linearity test and significance of regression. The result of analysis showed that there is direct effect of task commitment on work discipline with path coefficient 0.086 to the head master of madrasah ibtidaiyah in Deli Serdang Regency. The implication of this research result explains that the improvement of work discipline of Islamic Elementary School Principal in Deli Serdang regency can be done by guaranteeing conducive organization climate, supportive management, effective communication channel and value system that support the fulfillment of creativity and work autonomy besides work environment that fosters mutual respects, helps and trusts in carrying out its duties.